1998
DOI: 10.1021/ac970823f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption versus Absorption of Polychlorinated Biphenyls onto Solid-Phase Microextraction Coatings

Abstract: Absorption-based polymeric solid-phase microextraction (SPME) fibers with poly(dimethylsiloxane) (PDMS) coatings were used to determine the partitioning coefficients of polychlorinated biphenyls (PCBs) between the sorptive fiber coatings and water. Previous models showing very good correlations between octanol-water partitioning coefficients (K(ow)) and absorption-based fiber-water partitioning coefficients (K(dv)) for low-molecular-weight analytes failed to predict K(dv) values for PCBs. In fact, K(dv) values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
43
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 6 publications
(17 reference statements)
10
43
2
Order By: Relevance
“…Nevertheless high molecular weight congeners like cb-180 with high octanol-water partition coefficients have small K fw . These results agree with those obtained by Yu Yang and co-workers [33] where K fw values were calculated for PDMS coating for different congeners from cb-8 to cb-209. Similar results were observed with a decrease in K fw for the high molecular congeners despite of the high log K ow .…”
Section: Analytessupporting
confidence: 92%
“…Nevertheless high molecular weight congeners like cb-180 with high octanol-water partition coefficients have small K fw . These results agree with those obtained by Yu Yang and co-workers [33] where K fw values were calculated for PDMS coating for different congeners from cb-8 to cb-209. Similar results were observed with a decrease in K fw for the high molecular congeners despite of the high log K ow .…”
Section: Analytessupporting
confidence: 92%
“…For a typical 100 m PDMS fiber, which is the most widely used fiber, the volume of the extraction phase is approximately 0.5 l. Consequently, the extraction efficiency for solutes that are partially water soluble is quite low [36]. For very polar compounds, however, competition can occur between the aqueous phase, the SPME fiber, the glass wall of the extraction vessel, and the surface of the polytetrafluoroethylene stir bar used to stir samples [37,38].…”
Section: Theorymentioning
confidence: 99%
“…PCBs (and also PAHs) are among the compounds with the lowest water solubility and are known to easily adsorb on glass or other surfaces (e.g., the stir bars used in SPME). We suspected this to be occurring in the experiments and data presented by Yang et al With increasing apolarity, compounds will adsorb more strongly on active surfaces and will increasingly be lost, which should explain the observed effect. It was already mentioned by Yang et al that the stir bars could not be reused since that causes contamination problems (by the adsorbed PCBs).…”
mentioning
confidence: 93%
“…Although this correlation seemed to hold for a wide range of solutes, for high-molecular-weight and very apolar solutes such as polyaromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs), the correlation between K O/W and K PDMS/W was no longer valid. For PCBs it was found that, with decreasing polarity (increasing K O/W of a factor of 4 × 10 4 ), the measured K PDMS/W decreased by a factor of 40, which would mean a misprediction in K PDMS/W of a factor 2 × 10 6 . The authors explained their data by assuming surface adsorption on the PDMS fibers instead of bulk partitioning (sorption) and emphasized by comparison of data from two PDMS fibers (7 and 100 μm) the validity of this model.…”
mentioning
confidence: 99%